1996
DOI: 10.2307/2265705
|View full text |Cite
|
Sign up to set email alerts
|

On the Strategy of "Eating Your Competitor": A Mathematical Analysis of Algal Mixotrophy

Abstract: Recent experimental evidence indicates the importance in some pelagic systems of mixotrophic protists that combine photosynthetic ability with the ability to ingest bacteria. If both bacteria and phytoplankton are mineral nutrient limited, this should provide the mixotrophs with the double benefit of combining removal of their competitor with ingestion of the limiting nutrient in pelleted form. It is the objective of this study to expand the classical theories of competition and predation to explore the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(145 citation statements)
references
References 25 publications
(17 reference statements)
7
134
0
Order By: Relevance
“…In the simulations presented here, the MNFs did not win by eating their competitors (eating the HNFs or nonphagotrophic microalgae; cf. Thingstad et al, 1996). Instead, they succeeded through a combination of cooperative nutrition and, especially in the low-P simulations, through having a disadvantageous stoichiometric content (i.e.…”
Section: Interpreting the Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the simulations presented here, the MNFs did not win by eating their competitors (eating the HNFs or nonphagotrophic microalgae; cf. Thingstad et al, 1996). Instead, they succeeded through a combination of cooperative nutrition and, especially in the low-P simulations, through having a disadvantageous stoichiometric content (i.e.…”
Section: Interpreting the Simulationsmentioning
confidence: 99%
“…they are auxotrophic; Croft et al, 2006). Furthermore, osmotrophy alone does not have a direct powerful impact on trophic dynamics, as does the act of killing and engulfing a prey item through phagocytosis (Thingstad et al, 1996).…”
mentioning
confidence: 99%
“…Following many decades of dichotomous classi cation of planktonic organisms as`autotrophs' and`heterotrophs' (Flynn et al, 2012), importance of mixotrophy in ecosystem functioning has been increasingly recognized (Mitra et al, 2014, and references therein). Mixotrophy has been addressed mainly by theoretical work so far (e.g., Thingstad et al, 1997;Flynn and Mitra, 2009;Crane and Grover, 2010;Berge et al, 2017). The recent work of Ward and Follows (2016) constitutes the rst example where mixotrophy is resolved in a global ocean model.…”
Section: Introductionmentioning
confidence: 99%
“…Mitra and Flynn (2010) have indeed shown that descriptions integrating physiological processes, with some degree of feedback to modulate the processes of phototrophy and heterotrophy, are needed to properly represent the qualitative behavior of mixotrophs. Among existing mixotrophic models, only those of Stickney et al (2000) and the "perfect beast" of Flynn and Mitra (2009) take the interactions between the two trophic modes into account; the others rely on additive descriptions of phototrophy and heterotrophy (Thingstad et al, 1996;Baretta-Bekker et al, 1998;Jost et al, 2004;Hammer and Pitchford, 2005;Crane and Grover, 2010;Ward et al, 2011;Våge et al, 2013).…”
Section: Non-constitutive Mixotrophymentioning
confidence: 99%
“…Most interest has been leveled at the potential impact of mixotrophs on the microbial food web structure and functioning, and the conditions under which mixotrophs may likely coexist with strict phototrophs and heterotrophs (Thingstad et al, 1996;BarettaBekker et al, 1998;Stickney et al, 2000;Jost et al, 2004;Hammer and Pitchford, 2005;Hood et al, 2006;Flynn and Mitra, 2009;Crane and Grover, 2010;Ward et al, 2011;Våge et al, 2013). By far the greater effort has been applied to CM organisms.…”
Section: Introductionmentioning
confidence: 99%